التصوير البصري للشعر السرد في العصر الإسلامي - عباس عليوي, أ .م. د. انتهاء (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2023)
يكاد يتفق الجميع على أنّ التصوير البصري يصل إلى البناء الفني المسبوك شكلاً ومضموناً وصولاً إلى النضج والاكتمال،اذ تخصصت في مجموعة من الشعراء الاسلاميين، ولاسيّما أولئك الذين شهدت لهم ابياتهم الشعرية الكثير من السردية، إنَّ دراسة الشعر الاسلامي والنهل منه غاية كثير من الباحثين والدارسين فهو منهل خصبٌ وارثٌ حَضاريٌ متعددُ الفنون لا يمكن نسيانه، والانشغال عنه، ومن هنا كانت الرغبة مبنية على دراسته وتعرف أثره من خلال مجموعة من شعرائه تميزت اشعارهم بالسرد الفني ،فاتسمت هذه دراسة فنية تحليلية وصفية تخصصت في مجموعة من الشعراء الاسلاميين، ولاسيّما أولئك الذين شهدت لهم ابياتهم الشعرية الكثير من السردية، إنَّ دراسة الشعر الاسلامي والنهل منه غاية كثير من الباحثين والدارسين فهو منهل خصبٌ وارثٌ حَضاريٌ متعددُ الفنون لا يمكن نسيانه ، والانشغال عنه، ومن هنا كانت الرغبة مبنية على دراسته وتعرف أثره من خلال مجموعة من شعرائه تميزت اشعارهم.   Everyone agrees that visual photography reaches the artistic structure formed in form and content until it reaches maturity and completion, as it specialized in a group of Islamic poets, especially those whose poetic verses witnessed a lot of narration. Studying Islamic poetry and drawing from it is the goal of many researchers and scholars. It is It is a fertile source and a multi-art cultural legacy that cannot be forgotten or distracted from. Hence, the desire was based on studying it and knowing its impact through a group of his poets whose poetry was distinguished by artistic narration. This was characterized by an artistic, analytical and descriptive study that specialized in a group of Islamic poets, especially those who witnessed them. Their poetic verses are many narratives. Studying Islamic poetry and drawing from it is the goal of many researchers and scholars. It is a fertile source and a multi-art cultural legacy that cannot be forgotten or distracted from. Hence, the desire was based on studying it and knowing its impact through a group of poets whose poetry was distinguished.